2005
DOI: 10.1111/j.1475-4991.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stock Market Fluctuations on the Adequacy of Retirement Wealth Accumulation

Abstract: This paper examines the relation between fluctuations in the aggregate value of equities and the adequacy of households' saving for retirement. Using more recent data than most studies on this topic, we find that many and perhaps most households appear to be saving adequate amounts for retirement, and that there is almost no link between aggregate equity values and the adequacy of retirement saving. A simulated 40 percent decline in stocks has little effect on the adequacy of saving. The substantial growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Engen, Gale, and Uccello (1999) Engen, Gale, and Uccello (1999), is still 72 percent, leading the authors to conclude that households are close to being adequately prepared for retirement. In an updated study, Engen, Gale, and Uccello (2002) found that the upswing in stock prices from 1995 to 1998 did not substantially alter their earlier findings on retirement income. This suggests that much of the increase in retirement wealth was concentrated among households who were already adequately prepared for retirement.…”
Section: Retirement Income Adequacymentioning
confidence: 74%
“…Engen, Gale, and Uccello (1999) Engen, Gale, and Uccello (1999), is still 72 percent, leading the authors to conclude that households are close to being adequately prepared for retirement. In an updated study, Engen, Gale, and Uccello (2002) found that the upswing in stock prices from 1995 to 1998 did not substantially alter their earlier findings on retirement income. This suggests that much of the increase in retirement wealth was concentrated among households who were already adequately prepared for retirement.…”
Section: Retirement Income Adequacymentioning
confidence: 74%
“…Engen, Gale and Uccello (2005) investigate the effects of stock market fluctuations on the adequacy of retirement wealth accumulation, and find that since those that do hold stocks are typically households with substantial wealth, fluctuations in stock market values can affect wealth without having much effect on households" ability to save for retirement. They simulate a stock market decline of 40% and find that this has a negligible impact on the share of households with inadequate wealth.…”
Section: Related Literaturementioning
confidence: 99%
“…In addition to the replacement-rate approach, the literature inlcudes a collection of papers comparing wealth patterns in the data with optimal accumulation patterns from a stochastic life cycle model (see Engen, Gale, andUccello, 1999, 2005;Scholz, Seshadri, and Khitatrakun, 2006). The advantage of this method is that it derives from theoretical principles: working households save the amount necessary to provide the maximum level of smoothed consumption over their expected lifetimes.…”
Section: Previous Notions Of Adequacymentioning
confidence: 99%
“…4 See Bernheim (1992); Munnell and Soto (2005); Mitchell and Moore (1998); Moore and Mitchell (2000). 5 See Engen, Gale, andUccello (1999, 2005); Scholz, Seshadri, and Khitatrakun (2006); Brady (2006). 6 Earlier studies have included estimates of DB and Social Security wealth, but not annuities, life insurance, welfare or future wages.…”
Section: Introductionmentioning
confidence: 99%